Antecedents to Online Purchase Intention: Moderating Role of Persuasion Knowledge - Tariq Jalees; Dr. Syed Asad Hussain; Muhammad Ehtesham Khan; Dr Atif Aziz; Saleem Ahmed (Research Journal of Psychology, 2025)
E-commerce has experienced significant growth over the past few years. Its size in 2023 was approximately $6.54 trillion, which is expected to surpass $12 trillion by 2030. Given its importance, we examined the impact of credibility, parasocial relationships, and self-disclosure on online purchase intention. We also examined the moderating role of persuasion knowledge on the relationship between parasocial relationship and online purchase intention. Using online social media, we collected a sample of 417. The study documents that “credibility, parasocial relationships, and self-disclosure” have a positive effect on online purchase intention. It also found that persuasion knowledge moderates the relationship between parasocial relationship and online purchase intention. Given its importance, we suggest the online vendors must recruit credible online spokespersons who have large followings.